THE ROLE OF STUDENT ASSISTANTS IN PROMOTING INTERACTIVE ENGLISH LEARNING - Maghfiroh, Rizkiana Intan Devi; Zakiyah, Ainun; Zainuddin, Zainuddin (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
This study explores the role of student assistants in enhancing interactive English learning at MA Bahrul Ulum, an Islamic senior high school operating within a pesantren-based educational system. Positioned as part of a collaborative teaching strategy, student assistants serve not only as academic support but also as facilitators who promote learner engagement through a variety of interactive approaches. Employing a qualitative descriptive methodology, data were collected through classroom observations, interviews with English teachers and teaching assistants, as well as student reflections. The findings indicate that student assistants contribute meaningfully to building a more dynamic and student-centered classroom. They incorporate strategies such as language games, group discussions, role-plays, and the use of digital tools to make lessons more engaging. These methods were found to lower students’ anxiety when speaking English and increase overall classroom participation. Despite challenges such as limited experience and time management difficulties, assistants were able to bridge the gap between formal instruction and informal, communicative language practice. Their presence also made learning more relatable, especially through peer-to-peer interaction. Furthermore, their efforts aligned with the goals of the Merdeka Curriculum, which encourages contextualized, independent, and meaningful learning. In the pesantren setting, student assistants successfully integrated Islamic values into language activities, making English instruction more culturally relevant. The study concludes that, with proper training and structured implementation, student assistantship programs have the potential to significantly improve English language education in Islamic-based schools by enhancing motivation, fostering communication, and creating supportive learning environments.